Occupational Safety and Health Legislation: What Allied Health Professionals in Western Australia Need to Know - Brown, Kevin (2003)
The legislation dealing with occupational safety and health laws in Western Australia changed quite dramatically in the 1990s. This article provides an overview of the Occupational Safety and Health Act 1984 (WA) and describes the main features of the current legislation that apply to allied health professionals and some of the pertinent legal cases and recorded "significant incidents".